2017
DOI: 10.1111/evo.13268
|View full text |Cite
|
Sign up to set email alerts
|

Geographically structured genetic variation in theMedicago lupulinaEnsifermutualism

Abstract: Gene flow between genetically differentiated populations can maintain variation in species interactions, especially when population structure is congruent between interacting species. However, large-scale empirical comparisons of the population structure of interacting species are rare, particularly in positive interspecific interactions (mutualisms). One agriculturally and ecologically important mutualism is the partnership between legume plants and rhizobia. Through characterizing and comparing the populatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…We found that the similarity between the endosphere and rhizosphere varied among Medicago genotypes, suggesting that some genotypes might represent weaker lters than others. There is empirical evidence for variation along the specialist-generalist continuum within plant-microbe symbioses [75,76], as well as among plant species, with potential applied implications for the spread of invasive legumes [77,78]. Using ve genotypes of the plant Boechera stricta, Wagner et al [29] found signi cant genetic variation for metrics of microbiome diversity.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the similarity between the endosphere and rhizosphere varied among Medicago genotypes, suggesting that some genotypes might represent weaker lters than others. There is empirical evidence for variation along the specialist-generalist continuum within plant-microbe symbioses [75,76], as well as among plant species, with potential applied implications for the spread of invasive legumes [77,78]. Using ve genotypes of the plant Boechera stricta, Wagner et al [29] found signi cant genetic variation for metrics of microbiome diversity.…”
Section: Discussionmentioning
confidence: 99%
“…After its introduction to North America in the 1700s, M. lupulina expanded its range to occupy nitrogen‐poor areas of the continent's temperate and subtropical regions (Turkington & Cavers, ). In eastern North America, the relative frequencies of M. lupulina 's two symbiotic rhizobia species ( Ensifer medicae and E. meliloti ) vary along a northwest‐to‐southeast cline (Figure ) (Harrison, Wood, Heath, & Stinchcombe, in press). Medicago has a short generation time (Turkington & Cavers, ), its rhizobia are easily manipulated (Heath & Tiffin, ), an annotated genome is available in the genus (Young et al., ), and the genes involved in the rhizobial mutualism are extensively characterized (Cook et al., ; Mylona et al., ; Young et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In the facultative Medicago ‐rhizobia symbiosis, soil bacteria in the genus Ensifer (formerly Sinorhizobium ) (Young, ) fix atmospheric nitrogen for their plant hosts in exchange for carbohydrates and housing in specialized root organs called nodules (Mylona, Pawlowski, & Bisseling, ; van Rhijn & Vanderleyden, ). In eastern North America the relative frequencies of two principal symbionts ( Ensifer medicae and E. meliloti ) (Béna, Lyet, Huguet, & Olivieri, ) vary along a latitudinal cline (Figure ) (Harrison, Wood, Heath, & Stinchcombe,in press ), which may generate strong selection on Medicago populations to adapt to their local Ensifer species. The bacteria are essential for plant growth in nitrogen‐poor edaphic environments (Simonsen & Stinchcombe, ), and genes mediating the association experience strong selection in both Medicago and Ensifer (Bailly, Olivieri, De Mita, Cleyet‐Marel, & Béna, ; Bonhomme et al., ; De Mita, Santoni, Ronfort, & Bataillon, ; Epstein et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…There is empirical evidence for variation along the specialist-generalist continuum within plantmicrobe symbioses [75,76], as well as among plant species, with potential applied implications for the spread of invasive legumes [77,78]. Using five genotypes of the plant Boechera stricta, Wagner et al [29] found significant genetic variation for metrics of microbiome diversity.…”
Section: Discussionmentioning
confidence: 99%